RELASI GENDER DALAM KAJIAN ISLAM “THE TAO OF ISLAM, KARYA SACHIKO MURATA” - Atika Zuhrotus Sufiyana (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2017)
Listened more closely, Sachiko's cosmological and theological approach of murata flourished from the view of men and women, the word of Allah: